Pediatric Gliosarcoma With and Without Neurofibromatosis Type 1: A Whole-exome Comparison of 2 Patients. Issue 8 (23rd November 2021) - Graham, Richard T.; Bell, Erica H.; Webb, Amy; Zhao, Yue; Timmers, Cynthia; Fleming, Jessica L.; Sells, Blake E.; Robison, Nathan J.; Palmer, Joshua D.; Finlay, Jonathan L.; Chakravarti, Arnab
Abstract : Gliosarcoma is rare among pediatric patients and among individuals with Neurofibromatosis Type 1 (NF1). Here we compare 2 pediatric gliosarcoma patients, one of whom has NF1. We performed whole-exome sequencing, methylation, and copy number analysis on tumor and blood for both patients. Whole-exome sequencing showed higher mutational burden in the tumor of the patient without NF1. Copy number analysis showed differences in chromosomal losses/gains between the tumors. Neither tumor showed O6-methylguanine-DNA methyltransferase ( MGMT ) promoter methylation. The NF1 patient survived without progression while the other expired. This is the first reported case of gliosarcoma in a child with NF1.